Association between statistical significance and time to publication among systematic reviews: a study protocol for a meta-epidemiological investigation - Tsujimoto, Yasushi (BMJ Open, 2017)
INTRODUCTION: Many studies have indicated the impact of bias in dissemination and publication in medical research. Existence of such bias among clinical trials has been repeatedly pointed out, but it has not been well studied in the field of systematic reviews (SRs). We therefore aim to investigate whether or not time lag bias and publication bias in SRs based on statistical significance in results exist. In addition, we will examine at what stage of paper publication process such bias, if any, creeps in. METHOD AND ANALYSIS: The present study is a meta-epidemiological study. We will include all SRs of interventions registered in the international prospective register of SRs (PROSPERO) before December 2014 if the SR has completed its analysis irrespective of its publication status. All contact authors of eligible SRs will be asked to participate in a survey administered through the Internet. Our primary outcome is time from protocol registration to full publication of SR as a journal article, defined as time from the registration date to the acceptance date among all the relevant SRs. We will examine the impact of statistically significant findings on the primary outcomes through time to event analyses. ETHICS AND DISSEMINATION: Ethics approval will be obtained from the Ethical Committee of the Kyoto University Graduate School of Medicine. This protocol has been registered in the University Hospital Medical Information Network Clinical Trials Registry. We will publish our findings in a peer-reviewed journal and also may present them at conferences. Trial registration number: UMIN000028325